Phytochemical studies and in vitro activity of Asparagus racemosus - Kafle, Arjun; Kalauni, Surya K; Manandhar, Mangala Devi (Journal of Nepal Pharmaceutical Association, 2012)
Phytochemical and biological screening of root of Asparagus racemosus was studied. The brine shrimp bioassay of its various extracts showed that the methanol (MeOH) extract was biologically active. The column chromatography of hexane, acetone and methanol extracts resulted in the isolation of 9- hexadecanoic acid-9-octadecenylester (Z,Z), ?-Sitosterol, stigmasterol-3-O-?-D-glucopyranoside and diosgenin. The estimation of saponin in the root of Asparagus racemosus has also been carried out. DOI: http://dx.doi.org/10.3126/jnpa.v26i1.6632 JNPA. XXVI(1) 2012 48-53